Les mutations foncières et immobilières au pays du Mont-Blanc entre 2001 et 2008 - Isabelle André-Poyaud; Sylvie Duvillard; Antonin Lorioux (Revue de Géographie Alpine)
The aim of this contribution is to present a summary of the changes in property ownership that have occurred in a tourist area in the high mountains. Priority is given in the text to the analysis of data by taking advantage of a database recently made available on the knowledge market by the Notarial Office of France (Notariat de France). The geographer will find in it matters to reflect upon. First of all, a communal pattern that is to be explained by social qualitative variables (geographical origin of the individuals) emerges from the mapping of the total transactions. The socio-spatial fragmentation is the result of exchange systems for properties that reveal two competing residential processes. The article aims to demonstrate how a selective sorting process operates between communes, one group specialising in welcoming local populations, the other group rejecting the same populations at their outskirts. The analysis of property transactions on this scale indicates the obvious adjustment that exists between potential local demand and accessible supply. These are among the many aspects subject to the wisdom of politicians since they are preoccupied with the question of access of the local population to property (land and buildings) and the cohesion of their region.